Negotiation model for knowledge management system using computational collective intelligence and ontology-based reasoning: case study of SONATRACH AVAL. (2016) - Taghezout, Noria; Houari, Nawal Sad; Nador, Aissa
This paper presents an agent-based approach that facilitates knowledge management and decision making in maintenance field by enabling the collaboration and negotiation between experts in SONATRACH AVAL. The main objective of the suggested model is to treat the business rules with semantic errors, expert agents are asked to negotiate in order to accept or refuse a modification of rules. To do so, the expert manager can be represented by an intelligent agent that negotiates with experts (participants). We propose an interactive negotiation model utilising an extended version of the contract net protocol (CNP) and an ontology named OntoloG. The experimental results show that the developed computation collective intelligence approach is very interesting and efficient for expert collaboration in the well-known petroleum enterprise in Algeria (SONATRACH).